Impact of Terrorism on Students: A Case of Secondary School Students in District Bunirdents in District Bunir - Fazal Hayat; Shahji Ahmad; Samiullah Sarwar (Institute of Business Management, 2020)
The study sought to explore the incidents of terrorism causing fear among secondary school students in district Bunir to recognize the impact of terrorism on secondary school students in terms of their learning behavior and pattern. From the district of Bunir, students currently studying in 10th grade from 69 public sectors secondary school were approached randomly for the data collection associated with the incidents of terrorism causing fear among students and the influence of those incidents of terrorism on students' learning behaviour. The finding of the study illustrates that different aspects of terrorism including students' self-exposure, bomb blasts during school timing, and news regarding suicide bombers statistically significantly affect the student learning behaviour by increasing their fear. As schools' heads, teachers, parents, and media are expected to play a positive role in encouraging students to participate in the teaching-learning process without any fear and anxiety. The government is also recommended to take steps such as scholarship, abroad tours and financial assistance to increase the encouragement among the affected students.